Analysis of the sharia supervisory board’s characteristics and intellectual capital on maqashid sharia performance at islamic commercial banks in Indonesia - Marhamah, Annisa Fitri; Andraeny, Dita (Proceeding International Conference on Accounting and Finance, 2024)
This study aims to analyze the performance of maqashid sharia in terms of the characteristics of the Sharia Supervisory Board at Islamic Commercial Banks in Indonesia for the period 2017-2022. The independent variables studied are the characteristics of the Sharia Supervisory Board consisting of SSB size, SSB cross-membership, SSB education, SSB expertise, SSB reputation, SSB rotation, and SSB remuneration and using bank size and bank age as control variables. This study used purposive sampling method and obtained 8 Islamic Commercial Banks in Indonesia as the sample. The analysis technique used is panel data regression with e-views 12 software. In this study, the measurement of maqashid sharia performance uses two concepts, namely social requirements, and legal requirements. The results showed that SSB cross membership, SSB education, SSB remuneration affect the performance of maqashid Sharia. While SSB size, SSB expertise, SSB reputation, SSB rotation, and intellectual capital have no effect on maqashid sharia performance.